2014
DOI: 10.1111/ajt.12709
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Antibody-Mediated Rejection in Kidney Transplant Recipients With Anti-HLA-C Donor-Specific Antibodies

Abstract: Anti‐HLA donor‐specific antibodies (DSAs) cause acute and chronic antibody‐mediated rejection (AMR). However, the clinical relevance of anti‐HLA‐C antibodies remains unclear. We evaluated the clinical relevance of the presence of anti‐HLA‐C DSA at day 0 in renal transplant recipients. In this retrospective, case‐controlled study, 608 patients who underwent kidney transplantation between August 2008 and March 2012 were screened for the presence of isolated anti‐HLA‐C DSA at day 0. A total of 22 renal transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 15 publications
(20 reference statements)
1
25
2
1
Order By: Relevance
“…Our data reached similar results of these previous studies, confirming that DSA-Cw is associated with a similar incidence of AMR and impact on graft survival in comparison with “classical” DSA against class I[9,10]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data reached similar results of these previous studies, confirming that DSA-Cw is associated with a similar incidence of AMR and impact on graft survival in comparison with “classical” DSA against class I[9,10]. …”
Section: Discussionsupporting
confidence: 91%
“…Even so, the median time of follow up was relatively short and may have underestimated the incidence of rejection. Aubert et al[9] evaluated retrospectively 22 renal transplant recipients with isolated antiHLA-Cw DSA at day 0 of renal transplant, comparing them with 88 allosensitized patients with no preformed DSA (control group), and followed for a period of 1 year. Acute AMR was diagnosed in six patients (27.3%) in patients with DSA-Cw vs 9% in those without DSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Second, data on the clinical relevance of anti-HLACw antibodies are sparse. A retrospective casecontrol study of 22 patients with an isolated anti-HLA-Cw DSA at time of transplant reported an increased rate of antibody-mediated rejection, 5 although confirmation in a prospective study is awaited. Third, the role of non-HLA alloantigens is still being explored in solid-organ transplant.…”
Section: Discussionmentioning
confidence: 99%